The Importance Of State Work In The Judicial Function (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The judiciary is considered a social necessity whose importance appears through its function in protecting the legal system and achieving justice by removing obstacles or symptoms preventing its enforcement. The diversity of the symptoms of the enforcement of the legal system leads to the multiplicity of the functions of the judicial office, as the work of this office aims to achieve the judicial protection of the law itself.This protection appears either through judicial actions, temporary actions, or state action. So that the judicial work protects the legal rights and centers, while the temporary work removes the symptom of the risk of delay in protecting those rights and legal centers. As for the state work, it confronts the symptom of the individual’s lack of will or its inability to conduct business and behavior, by interfering with the state of the individual carrying out the activity or interfering with the same activity that the individual wants to do. This, in turn, contributes to the individual’s exercise and preservation of their rights, and overcomes the obstacle to the automatic enforcement of the law.